Evaluation of Fluorine-18-Labeled α1(I)-N-Telopeptide Analogs as Substrate-Based Radiotracers for PET Imaging of Melanoma-Associated Lysyl Oxidase - Kuchar, Manuela; Neuber, Christin; Belter, Birgit; Bergmann, Ralf; Lenk, Jens; Wodtke, Robert; Kniess, Torsten; Steinbach, Jörg; Pietzsch, Jens; Löser, Reik (Frontiers in Chemistry, 2018)
Accumulating evidence suggests an unequivocal role of lysyl oxidases as key players of tumor progression and metastasis, which renders this enzyme family highly attractive for targeted non-invasive functional imaging of tumors. Considering their function in matrix remodeling, malignant melanoma appears as particularly interesting neoplasia in this respect. For the development of radiotracers that enable PET imaging of the melanoma-associated lysyl oxidase activity, substrates derived from the type I collagen α1 N-telopeptide were labeled with fluorine-18 using N-succinimidyl 4-[18F]fluorobenzoate ([18F]SFB) as prosthetic reagent. With regards to potential crosslinking to tumor-associated collagen in vivo, their interaction with triple-helical type I collagen was studied by SPR. A mouse model of human melanoma was established on the basis of the A375 cell line, for which the expression of the oncologically relevant lysyl oxidase isoforms LOX and LOXL2 was demonstrated in Western blot and immunohistochemical experiments. The radiopharmacological profiles of the peptidic radiotracers were evaluated in normal rats and A375 melanoma-bearing mice by ex vivo metabolite analysis, whole-body biodistribution studies and dynamic PET imaging. Out of three 18F-labeled telopeptide analogs, the one with the most favorable substrate properties has shown favorable tumor uptake and tumor-to-muscle ratio. Lysyl oxidase-mediated tumor uptake was proven by pharmacological inhibition using β-aminopropionitrile and by employing negative-control analogs of impeded or abolished targeting capability. The latter were obtained by substituting the lysine residue by ornithine and norleucine, respectively. Comparing the tumor uptake of the lysine-containing peptide with that of the non-functional analogs indicate the feasibility of lysyl oxidase imaging in melanoma using substrate-based radiotracers.